Clinical and microbial study of reinforced 3D-printed maxillary denture base resin: a randomized trial - Eman Mohamed Ahmed Teama; Hoda Mohamed Amin Rashad; Eman Abd El-salam Mohamed Shakal; Eman Elsayed Hegazy (BMC Oral Health)
Abstract Statement of problem The 3D-printed denture base resin needed reinforcement. Purpose To evaluate the effects of adding nano ZrO2 and nano TiO2 on microbial colonization and patient satisfaction with 3D-printed maxillary complete dentures. Materials and methods Twenty-four patients who needed complete dentures were randomly distributed into three equal groups. Group I: Patients used maxillary complete dentures 3D printed without the addition of any additives. Group II: Patients used maxillary complete dentures 3D after reinforcement by Nano-ZrO2 (0.4%) by weight. Group III: Patients used maxillary complete dentures 3D printed after reinforcement by Nano-TiO2 (0.4%) by weight. For microbial evaluation, a cotton swab was taken from the mucosa of the palate and the intaglio surface of maxillary dentures, and microbial colonization was evaluated by calculating the number of colony-forming units of S. aureus on mannitol salt agar plates and C. albicans on Sabouraud’s dextrose agar plates after 48 h of incubation at insertion, 6 months, 12 months and 18 months. Patient satisfaction was evaluated 15 days after insertion and at 6, 12, and 18 months. The values of microbial colonization and patient satisfaction were analyzed via repeated-measures ANOVA followed by Tukey’s multiple comparison test. Results No significant differences in microbial colonization were detected among the three groups concerning Staphylococcus aureus in the palatal mucosa. There was a significant difference between Group I, the lowest antimicrobial group, and the other groups, while between Groups II and III, there was no significant difference in the number of S. aureus on the fitting surface of the denture. There were significant differences between Group II, the highest antifungal group, and the other groups at 12 and 18 months concerning Candida albicans in the palate and in the dentures. There was a significant difference in patient satisfaction between Group I, the lowest, and the other groups, whereas there was no significant difference between Groups II and III. Conclusion Compared with the other groups, the nano-ZrO2 group presented greater antimicrobial effects until 18 months, whereas the nano-TiO2 group presented antibacterial effects until 18 months and antifungal effects until 6 months. The addition of nano-ZrO2 and nano-TiO2 to 3D-printed denture base resin improved the aesthetic, speech, masticatory efficiency, hygiene, and comfort of patients. Trial registration The trial was registered in the Clinical Trials Registry under the number NCT06921577 on 10/04/2025 (retrospective registration).